Hybrid siliconized–epoxidized EPDM/polyurethane (eEPDM-g-APTES/HTPDMS/PU) matrices for potential application in cable insulation. Issue 8 (October 2020) - Vadivel, Manokaran; Kumar, Moses Suresh Chandra; Mohaideen, Jabbar Abbas; Alagar, Muthukaruppan; Sankarganesh, Murugesan; Raja, Jeyaraj Dhaveethu
Hybrid matrices (epoxidized of ethylene–propylene–diene monomer (eEPDM) -g- aminopropyltriethoxysilane (APTES)/hydroxyl terminated polydimethylsiloxane (HTPDMS)/polyurethane (PU)) were developed based on eEPDM with 3-APTES coupling agent and varying weight percentages (0.75, 1.50, 2.25, and 3.00 wt%) of PU prepolymer as coreactant using 7.5 wt% of HTPDMS as chain extender using suitable experimental conditions. The formation of hybrid matrices and their structure were characterized by Fourier transform infrared (FTIR). The thermal and morphological properties of the hybrid matrices were analyzed using differential scanning calorimetry and scanning electron microscope, respectively. Mechanical properties (tensile strength, elongation at break (%), Young's modulus, and hardness) were characterized as per ASTM standards. Data resulted from mechanical studies, it was noticed that the incorporation of 3-APTES, HTPDMS, and PU into eEPDM has improved the elongation at break (%) and lowered the values of tensile strength, Young's modulus, and hardness according to the percentage concentration. Morphological studies indicate the presence of heterogeneous morphology. Data obtained from different studies, it suggested that the hybrid matrices developed in the present work can be used as cable insulates for high-performance industrial and engineering applications.